Pengaruh Lama Pengeringan Daun Beluntas dan Jahe Terhadap Karakteristik Fisikokimia dan Organoleptik Minuman Herbal - Ilhami Khurniyati, Maylina; Irfan Bagus Prasetyo, Muhammad (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Beluntas leaves and ginger are natural ingredients rich in bioactive compounds and have the potential as functional drinks. Drying is an important step in maintaining the quality of these active compounds. This study aims to determine the effect of drying time on the characteristics of pH, antioxidant activity, and organoleptic properties of a mixture of beluntas leaves and ginger. The methodology used is an experimental design with variations in drying time, followed by pH analysis, antioxidant activity test using the DPPH method, and organoleptic tests including aroma, color, taste, and aftertaste. The results showed that drying time had a significant effect on pH values and antioxidant activity, and affected organoleptic attributes. Drying for too long reduces antioxidant activity and gives an undesirable aftertaste. The conclusion of this study is the need to determine the optimal drying time to maintain the physicochemical and sensory quality of the product.